Sucker production and activation techniques in banana ( Musa spp. ) - Bhende Siddhesh Shamrao (Department of Pomology and Floriculture, College of Horticulture, 2016)
The studies on “Sucker production and activation techniques in banana (Musa spp.)” taken up at the Central Orchard of the College of Horticulture, Vellanikkara and at Regional Agricultural Research Station (RARS), Kumarakom, Kottayam during January 2013 to September 2015. These studies were taken up exclusively for a basic understanding of the sucker genesis (origin), variation in sucker production of important cultivated clones with different ploidy and genomic constitution, photosynthate and nutrient allocatory pattern to different suckers using 14 C and 32 P and for probing the effects of physical and cultural methods (manurial doses) of sucker activation techniques. Among the different clones tested in the studies for sucker production, Karpooravalli (ABB) recorded the highest number of suckers followed by Njalipoovan (AB), Nendran (AAB), Kadali (AA), Robusta (AAA) and Bodles altafort (AAAA) respectively. Suckering habit was positively correlated with decreasing ploidy level and an increase in the M. balbisiana blood in the genomic constitution of the particular clone. Kadali (AA) recorded the highest sucker production followed by Robusta (AAA) and Bodles altafort (AAAA) within the M. accuminata ploidy. In diploids, Njalipoovan (AB) recorded the highest number of suckers over Kadali (AA) and in triploids, Karpooravalli (ABB) recorded the higher number of suckers followed by Nendran (AAB) and Robusta (AAA) respectively. Differences in sucker production were observed between the different clones with respect to planting seasons. Kadali (AA), Njalipoovan (AB), and Robusta (AAA) recorded the higher number of suckers in Sept-Oct planting, whereas in case of Nendran (AAB) and Karpooravalli (ABB), Feb-March planting recorded the best sucker production. Bodles altafort (AAAA) recorded almost the same number of suckers in all the three plantings. Morphological characters like plant height, collar girth and total number of leaves recorded very strong and positive correlation with sucker characters but negative correlation was observed with average leaf production interval. Bunch weight recorded strong significant negative correlation with improved sucker production and was positively correlated with number of dead suckers. Number ofdead suckers produced were found positively correlated with plant height, collar girth, ‘D’ leaf area and average leaf production interval and almost a similar correlation between these characters was observed in PCA and factor analysis. The cluster analysis of six banana varieties, planted in three different seasons (18 entries) revealed that the clones fell in four distinct clusters. NJALI-1, NJALI-2, NJALI-3, NEND-1, NEND-3, KARP-2 and KARP-3 were grouped in the first cluster. ROB-1, ROB-2, ROB-3 and KAD-1 were grouped in the second cluster. KAD-2, KAD-3 and NEND-2 formed the next cluster and BOD-1, BOD-2, BOD-3 and KARP-1 formed the last cluster. In case of cluster analysis obtained from pooled data of six banana varieties planted in three seasons (6 entries), first cluster was composed of NJALI, NEND and KARP. Cluster II, III and IV were composed of KAD, ROB, BOD respectively and almost similar grouping was obtained from PCA and factor analysis. PCA and factor analysis revealed that diversity contributed by different banana traits for sucker production in first, second and third components was 46.8, 27.0 and 12.2 per cent respectively. The first three major factors / principle components contributed total 85.9 per cent of the diversity. PCA and factor analysis revealed that average dry weight of quality suckers, average dry weight of total suckers, total number of suckers produced, number of underdeveloped suckers produced, total number of leaves produced, number of quality suckers produced, plant height and collar girth characters recorded their dominance in first component/factor and were the most important traits for deciding the diversity of banana varieties in the present study. Communality values in factor analysis clearly revealed that the collar girth was the high relative contributory trait for deciding sucker yield in banana. The origin or genesis and early development of the sucker primordia was observed in the cortex region of the mother corm and this is the first confirmatory report on this aspect. The photosynthesis partitioning from the mother plant to daughter suckers using 14 C in six sucker retention intact system revealed that the last formed suckers got maximum share of photosynthates. In case of 1 st , 2 nd and 3 rd suckerremoval as an individual treatments, more allocation of the photosynthates was observed to the immediately next sucker and when 4 th and 5 th suckers were removed 6 th and 3 rd suckers showed the highest recovery of 14 C, revealing the positional effects in garnering more photosynthate. This report on actual photosynthate translocation from the mother plant to the daughter suckers is also the first of its kind under actual field conditions. Again this is also the first report on the redistribution of photosynthates to daughter suckers as a consequence of individual sucker removal. The experiment conducted on nutrient cycling from mother plant to daughter suckers using 32 P at two different stages i.e. fortnight before harvest and at harvest again confirmed that the mother plant has a definite dominant role in the distribution of nutrients and also redistribution to the daughter suckers consequent to sucker removal that was more destructively observed when the bunch was retained or not harvested. The very high recovery of 32 P in the mother plant was due to the high recovery observed in the bunch. At a fortnight before harvest, in all the treatments the highest recoveries of 32 P was observed in the mother plants. When 1 st sucker was removed the next best recovery was observed in the 2 nd sucker followed by 4 th sucker, when 2 nd sucker was removed the next best recovery was observed in 4 th sucker, when 3 rd sucker was removed the next best recovery was seen in 1 st sucker followed by 2 nd sucker, when 4 th sucker was removed the 2 nd sucker resulted the next highest recovery followed by 5 th sucker and when 5 th sucker was removed the next highest recovery was observed in 1 st sucker. At the time of harvest the removal of 1 st sucker resulted the highest recovery of the activity in the mother plant followed by 2 nd sucker. Removal of 2 nd sucker resulted the highest recovery in the 1 st sucker and mother plant. The 3 rd sucker removal resulted the highest recovery in the 1 st sucker followed by 2 nd sucker, removal of 4 th sucker resulted the highest recovery in the 3 rd sucker followed by the mother plant. The removal of 5 th sucker resulted the highest recoveries in 2 nd and 4 th sucker.Both the studies on nutrient recycling revealed a trend of higher recovery in the immediately next sucker. The recovery was the highest in the mother plant in the studies on fortnight before harvest due to retention of the bunch. Nutrient redistribution pattern to daughter suckers as a consequence of phased removal of individual suckers is also being reported for the first time. With respect to the sucker activation techniques, the studies on physical methods revealed that replanting the entire clump in trenches in oblique manner ten days after harvest produced maximum total number as well as quality suckers which performed equally well with the next best treatment of cutting the pseudostem at half height ten days after harvest. However, the latter treatment was the most economical one. In case of cultural methods (manurial doses) of sucker activation, application of NPK mixture (17: 17: 17) @ 5 and 10 g N equivalent clump -1 yielded maximum number of total as well as quality suckers, but the lower dose was found to be more economical based on B: C ratio.